Unlocking The Human Urobiome: Impact On Health and Disease- A Review: Life Sciences-Microbiology - Ramalingam, Aishwarya J; Khan, Sameena; J, Manonmoney; R, Archana (International Journal of Life Science and Pharma Research, 2022)
The urinary microbiome or the urobiome are the group of microbes present in the urinary tract. They came into the limelight in the last decade due to advances in diagnostic technologies. Two complementary assays are widely used for research in urobiomes. Next-generation sequencing (NGS) of 16S ribosomal RNA (rRNA) paired with enhanced urine culture techniques (EUCT) are widely employed for research. This has paved the way for investigations on sterile body sites such as urine thereby breaking the myth of urine being considered sterile. EUCT, such as expanded quantitative urine culture (EQUC) contributed to the evidence that the microbes detected by the NGS are still alive. EQUC has been employed in clinical laboratories since the last decade and is indicated only when there are unexplained clinical symptoms and conventional urine culture is negative. Our aim is to have a comprehensive review study on the urobiome concerning health, its association with urological pathologies. Our main objective is to collect review and research articles using databases and review them for obtaining in-depth knowledge of the urobiome as well as to identify possible alternate study areas. The urobiome is a new area with minimal information available. This review helps the researcher to comprehend this upcoming area easily. Investigations into urobiome research, however, could have a considerable impact on our understanding of the pathogenesis of urogenital disorders and even reveal novel possibilities. Thus, the forthcoming years will open a ripe ground for future research into diagnosis, treatment and prevention strategies for urological pathologies.